ORAL CORTICOSTEROIDS AND THE LONG-TERM RISK OF CATARACT: A COMPREHENSIVE SYSTEMATIC REVIEW - Mohammad Ilham Efendi, Raden; Astry Evangelia, Ruth; Youndra Darmawan, Albab (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A cataract can lead to visual deterioration, resulting in reduced vision capacity and partial or complete reversible vision loss. The most commonly associated risk factors for cataract include aging, diabetic retinopathy, glaucoma, and some medications such as glucocorticoids. Glucocorticoids are utilized in a variety of disorders, as long- and short-term, treatment such as topical ocular steroid usage, allergic rhinitis and inflammatory bowel disease as a result, the chance of cataract may increase and put a significant burden in countries. The aim: This study aims to show about oral corticosteroids and the long-term risk of cataract. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 79 articles, whereas the results of our search on SagePub brought up 208 articles, on Google Scholar brought up 26.000 articles. The results of the search conducted for the last year of 2014 yielded a total 25 articles for PubMed, 73 articles for SagePub, and 18.000 articles for Google Scholar. The result based on title screening, a total 2 articles for PubMed, 36 articles for SagePub, and 397 for Google Scholar. In the end, we get a total of 10 papers. We included five research that suitable the criteria. Conclusion: Using glucocorticoids either as inhaler and/or orally will increase the risk and prevalence of posterior subcapsular cataract and other ocular complications such as glaucoma.